Lithics : macroscopic approaches to analysis - Andrefsky, William, Jr., 1955- (Cambridge manuals in archaeology., 2005)
"Lithics, the practice of stone artifact analysis, has undergone many changes in recent years with the development of new techniques of analysis and the re-assessment of older techniques. This book is a fully updated and revised edition of William Andrefsky Jr.'s ground-breaking manual on lithic analysis. Designed for students and professional archaeologists, this highly illustrated book explains the fundamental principles of the measurement, recording, and analysis of stone tools and stone tool production debris. Introducing the reader to lithic raw materials, classification, terminology, and key concepts, it comprehensively explores methods and techniques, presenting detailed case studies of lithic analysis from around the world. It examines new emerging techniques, such as the advances being made in lithic debitage analysis and lithic tool analysis, and includes a new section on stone tool functional studies. An extensive and expanded glossary makes this book an invaluable reference for archaeologists at all levels."--Jacket